Silicene Nanoribbons on an Insulating Thin Film. (16th November 2020) - Quertite, Khalid; Enriquez, Hanna; Trcera, Nicolas; Tong, Yongfeng; Bendounan, Azzedine; Mayne, Andrew J.; Dujardin, Gérald; Lagarde, Pierre; El kenz, Abdallah; Benyoussef, Abdelilah; Dappe, Yannick J.; Kara, Abdelkader; et al.
Abstract: Silicene, a new 2D material has attracted intense research because of the ubiquitous use of silicon in modern technology. However, producing free‐standing silicene has proved to be a huge challenge. Until now, silicene could be synthesized only on metal surfaces where it naturally forms strong interactions with the metal substrate that modify its electronic properties. Here, the authors report the first experimental evidence of silicene nanoribbons on an insulating NaCl thin film. This work represents a major breakthrough, for the study of the intrinsic properties of silicene, and by extension to other 2D materials that have so far only been grown on metal surfaces. Abstract : For the first time, silicene nanoribbons are grown on an insulating NaCl thin film. The scanning tunneling microscopy image shows a hexagonal structure, confirmed by the density functional theory calculations. Photoemission and fine structure spectroscopy reveal that the interaction between the silicene and the NaCl is weak. The formation of free‐standing silicene decoupled from the metal substrate presents a major breakthrough.